Radiologic Evaluation of the Anterior and Posterior Ethmoidal Foramen and Optic Canal by Paranasal Sinus Computed Tomography Scan among Adult Filipinos - Palacios, Maria Katerina; Amable, Jay Pee; Capio, Kea (Philippine journal of otolaryngology head & neck surgery, 2022)
ABSTRACT Objective: To measure the average distances from anterior lacrimal crest (ALC) to anterior ethmoidal foramen (AEF), anterior ethmoidal foramen to posterior ethmoidal foramen (PEF) and posterior ethmoidal foramen to optic canal (OC) using plain paranasal sinus (PNS) computed tomography (CT) scans of adults in a tertiary private hospital in the Philippines. Methods: Design: Retrospective review of plain PNS CT scans Setting: Tertiary Private Teaching Hospital Participants: One hundred four (104) plain PNS CT scans from January 2018 to December 2020 were considered for inclusion. Results: Of the 104 PNS CT scans, 35 were excluded - seven for age less than eighteen, six for undistinguishable PEF and twenty-two for chronic rhinosinusitis. The remaining 69 PNS CT scans demonstrated identifiable structures, with overall average distances from ALC to AEF of 23.71 ± 2.43 mm, AEF to PEF of 10.87 ± 2.39 mm and PEF to OC of 7.39 ± 2.28 mm. Conclusion: Our study suggests average distances for localization of vital structures such as the anterior ethmoidal artery, posterior ethmoidal artery and optic nerve among Filipinos. Because of considerable variation between and within sexes, individual measurements should still be obtained for each patient in performing endonasal, skull base and orbital surgery.